CFD: A New Challenge in Bioprocess Engineering (2018)
ABSTRACT: Computational Fluid Dynamics (CFD) is a powerful tool based on mathematical applications for modeling transient and spatial transport modes such as mass, momentum and heat transfer in multiphase fluids. Currently, CFD has been applied for biological engineering processes. In this paper, a review of Bioprocess engineering applications in computational fluid dynamics (CFD) is presented, including important steps such as sterilization, mixing in CSTR, mass transfer and biochemical reactions applications.